COMPARISON OF ADJUVANT EFFICACY IN STREPTOCOCCUS SUIS VACCINATION IN MICE: SECONDARY ANTIBODY TITER ANALYSIS USING ANTIGEN SUPERNATANT BASED ELISA - I Made Yudhara Teresnanda; I Nengah Kerta Besung; Putu Devi Jayanti; I Gusti Ngurah Kade Mahardika; Ni Ketut Suwiti (Buletin Veteriner Udayana, 2025)
Streptococcus suis is a Gram-positive zoonotic bacterium that causes various diseases in pigs, such as meningitis, arthritis, and septicemia, which affect animal health and the economic viability of the livestock industry. Vaccination, supported by appropriate adjuvants, is an effective control strategy to enhance immune responses. This study aimed to evaluate secondary antibody responses in mice vaccinated with S. suis antigen using two different adjuvants, Montanide™ ISA 201 VG and Montanide™ Gel 01, and to analyze the dynamics of antibody titer increase. Eighteen mice were divided into three treatment groups: a control group receiving adjuvant without antigen, a vaccine group with Montanide™ ISA 201 VG, and a vaccine group with Montanide™ Gel 01. Vaccination was administered twice, and blood samples were collected weekly for four weeks post-vaccination. Antibody titers specific to S. suis supernatant antigen were measured using the ELISA method. Data were analyzed using ANOVA, Least Significant Difference (LSD) test, and regression analysis. The results showed that both adjuvants significantly increased antibody titers compared to the control (p<0.05), with a progressive increase in titer levels. Montanide™ ISA 201 VG provided sustained stimulation through a depot effect, while Montanide™ Gel 01 elicited an effective immune activation with minimal local reactions. In conclusion, the combination of S. suis antigen with both adjuvants significantly enhanced humoral immune responses, supporting the potential of both adjuvants to improve S. suis vaccine efficacy. Further research is needed to determine the optimal dose and duration of post-vaccination immune protection.